Pengenalan diabetes mellitus beserta pengobatannya dengan daun kersen - Muammar Khadafi; Ruri Putri Mariska; Reren Sagita Hermawan; Rayhanil Jannah; Khairinnisa Al Adha; Tuti Habibil Jannah (Jurnal Pengabdian Harapan Ibu (JPHI), 2022)
People with diabetes mellitus continue to increase every year, according to the International Diabetes Federation (IDF) in 2019 there will be 463 million people in the world suffering from diabetes at the age of 20-79 years with a prevalence of 9.3%. Indonesia is ranked 7th out of 10 countries with the highest number of diabetics in the world. survey Based on filling out questionnaires from house to house, the problems experienced by the people of RT 09 and 26 of Mekar Jaya Village are in the form of a lack of community knowledge regarding diabetes and its treatment. Education about diabetes is important so that people can avoid the disease or can take appropriate treatment. Cherry leaf is one of the plants that is easily found in the neighborhood of RT 09 and 26. This plant can be used as an antidiabetic herbal medicine. For this reason, we carry out community service in the form of diabetes counseling and processing cherry leaves into herbal. The purpose of this disease is to increase public knowledge about diabetes. The method used is conducting counseling in the form of delivering material with lectures and ending with a question and answer session. The results obtained are that the public gets information in the form of prevention, treatment, and other important information about diabetes.